Replacing customs revenue with taxes on income and domestic consumption: The South African experience - Andreas Freytag; Krige Siebrits (Friedrich Schiller University Jena, Faculty of Economics and Business Administration, 2023)
The African Continental Free Trade Agreement (AfCFTA) was signed by 54 member states of the African Union and is the largest free trade area in the world. Among other things, dismantling tariffs will have effects on public revenues in member states; this will require a revenue transition from customs duties to other forms of public revenues such as income and value added taxes. This transition may be a politically difficult process. This paper analyses the process of revenue transition in South Africa after World War I and after the end of the Apartheid regime to improve understanding of the constraints to and effects of such a revenue transition. The transition in South Africa from a tax revenue structure anchored by customs revenue to one dominated by income taxes and taxes on domestic consumption was a protracted and unplanned process. The general revenue needs of the government led to the introduction of income taxes in 1914 and a broad-based consumption tax in 1979. In addition, excise taxes have been in use ever since the establishment of the Union of South Africa in 1910 and in recent times have become increasingly important for other purposes as well. Along with the shift in the role of customs duties from revenue-generating to protective instruments and fairly extensive use of non-tariff barriers, these developments meant that import taxes became markedly less important tax handles during the course of the 20th century. As a result, the revenue implications of the trade liberalisation process in the early 1990s were minor, and the implementation of AfCFTA would not be a large shock to government revenue in South Africa either.
Keywords: H20; H27; 330